MULTIMEDIA TECHNOLOGIES IN TEACHING OF PHYSICS - Taylanov, Nizom; Urazov, Abdixoliq (Физико-технологического образование, 2022)
Multimedia is the ability to work with different forms of information on a computer: color graphics, dynamic effects in text and graphics, sound output and synthesized music, animation, as well as full-length video clips and videos. Multimedia is a modern computer information technology that allows you to combine text, sound, video, graphics and animation into a single computer system